Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai di Puskesmas Simolawang Kota Surabaya - Karyanto, Catur (Seminar Nasional Manajemen, 2025)
This research aims to evaluate the effect of work discipline on employee performance at Puskesmas Simolawang, Surabaya City. Work discipline plays a crucial role in enhancing organizational effectiveness, particularly in the healthcare sector. The study uses a quantitative approach with simple linear regression analysis to determine the relationship between work discipline as the independent variable and employee performance as the dependent variable. Data were collected through questionnaires distributed to both medical and non-medical staff. The findings show the regression equation Y = 3.364 – 0.027X, indicating a negative relationship between work discipline and performance. However, the effect is statistically insignificant, with a t-value of -1.634 and a p-value of 0.110 (p > 0.05). The R² value is 0.063, which means that only 6.3% of the variation in employee performance is explained by work discipline. This suggests that other factors beyond work discipline may have a stronger influence on performance outcomes. The limitation of this study lies in the narrow scope, focusing only on one variable and one healthcare institution. Future research should explore additional factors such as motivation, leadership, or organizational culture. Practically, the study provides insight for healthcare managers to reassess and improve strategies in managing discipline and performance. Socially, it emphasizes the importance of understanding multiple dimensions affecting employee outcomes in public health institutions.